Understanding home, homeland, and family at the end of life: a qualitative study of older South Asians in East London - Ramasamy Venktasalu, Munikumar (2011)
Background: South Asians constitute the single largest ethnic minority group in the United Kingdom, yet little is known about their perspectives and experiences on end of life and its related care.